Student engagement with AI tools in learning: evidence from a large-scale Estonian survey - Granström, Mikk; Oppi, Piret (Frontiers in Education, 2025)
The rapid advancement and proliferation of generative artificial intelligence (AI) tools such as ChatGPT are reshaping the educational landscape, with students integrating these technologies into learning practices faster than curricula and institutional policies can adapt. This study presents the results of a large-scale national survey conducted in Estonia in 2024, involving 15,631 students from grades 6 to 12, to map the prevalence, purposes, and perceptions of AI use among school-aged learners. Estonia provides a unique context as one of the first countries in Europe to formally introduce AI literacy into its national curriculum. The study examined (1) the extent and purposes of AI tool usage, and (2) how students’ attitudes toward AI’s usefulness, risks, and ethical implications differ across educational levels. Results show that most students have already used at least one AI tool, primarily for completing school assignments such as homework and essay writing. While upper secondary students reported greater awareness of both benefits and risks and higher engagement with AI, lower secondary students showed less exposure and may need more structured support. The findings suggest a potential implementation gap: students’ practices are evolving ahead of pedagogical frameworks, which could be associated with uncritical use and challenges for metacognitive engagement. The study highlights the urgent need for pedagogically grounded, age-appropriate AI integration strategies and emphasizes the importance of future research to examine AI’s associations with learning outcomes, motivation, and critical thinking. These findings provide a foundational baseline for future policy and practice as AI education becomes institutionalized.